The reproductive performance, mothering ability and productivity of crossbred and Tswana beef cows in Botswana - Light, D.; Buck, N.G.; Sethola, L.L. (Cambridge University Press, 1982)
The calving rates, survival and growth of calves of Brahman (344), Bonsmara (454), Simmental (601) and Tuli (276) crossbred cows, and pure Tswana (405), were collected for a 7-year period, 1974-80. Calving and survival rates for calves were 0.90, 0.88, 0.87, 0.87 and 0.82; and 0.94, 0.93, 0.96, 0.94 and 0.93, for Simmental, Tuli, Brahman and Bonsmara crossbreds, and pure Tswana, respectively. Their differences were not significant (P < 0.05). Calves produced by Simmental male and Bonsmara female crossbred cows were significantly heavier than those from Brahman male and Tuli female crossbred cows (P